A global optimization approach for sliding mode tuning and existence maps generation - Rosendo, Juan Luis (2020)
In this work, global optimization techniques based on interval arithmetic are proposed to analyze and synthesize sliding mode (SM) controllers. The proposed methodology allows generating a series of maps, called subpavings, which put in evidence the required relationships among tuning parameters, disturbances and control amplitude to fulfill the sufficient condition of SM in a guaranteed way. The a priori knowledge of the control power necessary to guarantee SM behavior of nonlinear systems despite parameter uncertainties and external disturbances is an advantage of this proposal compared to traditional tuning methods, which usually fall into over-sizing solutions. Although the methodology is developed in the context of conventional first-order SM controllers, it could be extended to any other SM design approach.